Assessment of integrated CO2 geologic storage and geothermal harvest in a semi-closed thin reservoir. (February 2022) - Chen, Mingjie; Al-Maktoumi, Ali; Izady, Azizallah
Highlights: Sensitivity of 8 performance indicators to well space and production rate are analyzed for 3 tiers of critical injection overpressures. Production rate controls produced heat flux while well space dominates total heat in lifespan. The requirement of produced CO2 cut > 0.94 can be met as long as well space is <800 m. Technical procedure on well placement and circulation scheme are given by using response surfaces. Abstract: CO2 plume geothermal (CPG) production built on the ongoing or completed Carbon Dioxide (CO2 ) geological storage (CGS) offers an emerging technique to harvest non-carbon renewable energy and offset CGS cost. Several studies on integrated CGS and CPG considered traditional 5-spot well placement in large-scale and thick saline formations with open boundaries. Very limited studies have been conducted on fault-compartmentalized, inclined thin reservoirs, which are widely available in oil/gas fields. Critical pressure management and risk of fault leakage have to be carefully evaluated dealing with such kind of geological structures. The aim of this study is to fill in this knowledge gap in the field of integrated CGS and CPG. A suite of model simulations is designed and experimented to assess CO2 sequestration and circulation in a fault-reservoir system under three levels of critical overpressure. Sensitivity of performance indictors to well space and circulation rate are quantitatively and continuously evaluated in their ranges using response surface method. Analysis of response surfaces yields a simple but efficient guidance for geothermal field planner and operator to find optimal well placement and operation scheme according to the priority of goals, including maximal energy production, desired heat energy capacity, expected lifespan.